2020
DOI: 10.2147/copd.s238457
|View full text |Cite
|
Sign up to set email alerts
|

<p>Malnutrition, Airflow Limitation and Severe Emphysema are Risks for Exacerbation of Chronic Obstructive Pulmonary Disease in Japanese Subjects: A Retrospective Single-Center Study</p>

Abstract: Background: Different characteristics of patients with chronic obstructive pulmonary disease (COPD) between Western and Japanese populations have been reported. Risk factors for COPD exacerbation have been reported in Western countries but have not been studied in Japan. Patients and Methods: We retrospectively examined risk factors for COPD exacerbation. A total of 156 Japanese patients were enrolled, and the records of 136 patients were analyzed. Results: In the exacerbation group (n=60), body mass index, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 36 publications
1
23
0
1
Order By: Relevance
“…The adverse impact of malnutrition on morbidity, mortality and QoL in a variety of diseases has already been recognized [ 18 , 19 , 20 ]. The available publications report associations between the above-mentioned disorders typical for the elderly population and malnutrition in patients with cardiovascular disease [ 18 ], respiratory disorders [ 19 ], or cancers [ 20 ], but few papers have been published on patients with rheumatic diseases. Therefore, we have undertaken to evaluate nutritional status, cognitive impairment, functional limitations, frailty syndrome severity, and their associations with QoL.…”
Section: Introductionmentioning
confidence: 99%
“…The adverse impact of malnutrition on morbidity, mortality and QoL in a variety of diseases has already been recognized [ 18 , 19 , 20 ]. The available publications report associations between the above-mentioned disorders typical for the elderly population and malnutrition in patients with cardiovascular disease [ 18 ], respiratory disorders [ 19 ], or cancers [ 20 ], but few papers have been published on patients with rheumatic diseases. Therefore, we have undertaken to evaluate nutritional status, cognitive impairment, functional limitations, frailty syndrome severity, and their associations with QoL.…”
Section: Introductionmentioning
confidence: 99%
“…A previous prospective study demonstrated that patients with a lower BMI or those who had a weight reduction during the previous year had an increased likelihood of having an exacerbation compared with patients whose weight was either unchanged or increased (26). In addition, there are reports that hypoalbuminemia and hypoproteinemia are independent risk factors of exacerbation (27,28). We could not find any data on the levels of protein, albumin, prealbumin, and retinol-binding protein, which have been considered as markers of visceral protein stores.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, CCI score > 2 and GSRs score > 2 increased the risk of intestinal ora disorders in stable COPD patients by 25.633 times and 17.113 times, respectively, whereas BMI > 23.25kg/m 2 and ALB > 32.5g/L might be protective factors, which decreased the risk of intestinal ora disorders in stable COPD patients by 0.090 times and 0.278 times, respectively. BMI is often regarded as indicator of the body's nutritional status and reports also demonstrated the association of low BMI with exacerbation in patients with COPD [11]. A 3-year South Korean study of follow-up BMI to predict the prognosis of COPD found that the decrease in BMI was independently related to the deterioration of COPD and the increase of mortality (HR = 3.167) [12].…”
Section: Discussionmentioning
confidence: 99%